2009
DOI: 10.1101/gr.089417.108
|View full text |Cite
|
Sign up to set email alerts
|

Targeted genome editing in human cells with zinc finger nucleases constructed via modular assembly

Abstract: Broad applications of zinc finger nuclease (ZFN) technology-which allows targeted genome editing-in research, medicine, and biotechnology are hampered by the lack of a convenient, rapid, and publicly available method for the synthesis of functional ZFNs. Here we describe an efficient and easy-to-practice modular-assembly method using publicly available zinc fingers to make ZFNs that can modify the DNA sequences of predetermined genomic sites in human cells. We synthesized and tested hundreds of ZFNs to target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
335
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 418 publications
(345 citation statements)
references
References 50 publications
7
335
1
2
Order By: Relevance
“…1 Two of the three reports cited provide data that enable calculation of failure rates for modular assembly. 2,3 Although it is true that modular assembly yielded ZFNs for ~25% of the DNA sites targeted, failure rates measured instead by the number of zinc finger proteins tested are remarkably consistent with those reported in our original Correspondence. 1 For example, at the human CCR5 gene, Kim et al screened 315 pairs of ZFNs for activity; 3 this large-scale effort yielded only a small number of functional ZFN pairs (93.3% failure rate for ZFN pairs tested).…”
Section: To the Editorsupporting
confidence: 75%
“…1 Two of the three reports cited provide data that enable calculation of failure rates for modular assembly. 2,3 Although it is true that modular assembly yielded ZFNs for ~25% of the DNA sites targeted, failure rates measured instead by the number of zinc finger proteins tested are remarkably consistent with those reported in our original Correspondence. 1 For example, at the human CCR5 gene, Kim et al screened 315 pairs of ZFNs for activity; 3 this large-scale effort yielded only a small number of functional ZFN pairs (93.3% failure rate for ZFN pairs tested).…”
Section: To the Editorsupporting
confidence: 75%
“…The T7E1 assay was performed as described previously 23 . In brief, PCR products amplified using genomic DNA were denatured at 95°C, reannealed at 16°C and incubated with 5 units of T7 Endonuclease I (New England BioLabs) for 20 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Engineered nuclease-induced mutations are detected by various methods, which include mismatch-sensitive Surveyor or T7 endonuclease I (T7E1) assays 23 , RFLP analysis 24 , fluorescent PCR 25 , DNA melting analysis 26 and Sanger and deep sequencing. The T7E1 and Surveyor assays are widely used but often underestimate mutation frequencies because the assays detect heteroduplexes (formed by the hybridization of mutant and wildtype sequences or two different mutant sequences); they fail to detect homoduplexes formed by the hybridization of two identical mutant sequences.…”
mentioning
confidence: 99%
“…To compare the activities of programmable nucleases expressed by minicircles versus conventional plasmids, we used pcDNA 3.0 ( Figure 1a) instead of the minicircle parental plasmid (Figure 1b) as the control vector because pcDNA 3.0 has been the primary vector used for programmable nuclease expression; [50][51][52] furthermore, the minicircle parental plasmid has not been used as an expression vector for programmable nucleases. Electrophoresis of the isolated minicircle vector showed that a major band of minicircle and a minor band of parental plasmid was present (Figure 1c).…”
Section: Preparation Of Minicircle Dna Encoding Zfns or Talensmentioning
confidence: 99%
“…We subcloned sequences encoding a pair of CCR5-targeting ZFNs (Z-224 19,50,53 ) and a pair of DGAT1-targeting TALENs into a minicircle parental plasmid and the pcDNA 3.0 plasmid; in both cases, expression of the programmable nuclease is driven by the cytomegalovirus (CMV) promoter. Detailed information about ZFN-224, which targets CCR5, has been previously described.…”
Section: Plasmids Encoding Zfns and Talensmentioning
confidence: 99%